Penerapan Data Mining Dalam Menentukan Calon Credit Marketing Oficer (CMO) Baru Di PT. WOM Finance Dengan Menggunakan Metode Asosiasi - Yuda Perwira (Jurnal Mantik Penusa, 2018)
Abstract Utilization of existing data in the information system to determine the prospective New Credit Marketing Officer (CMO) at PT. WOM Finance, it is not enough to only rely on operational data, we need a data analysis to explore the potential of existing information. In the system that is running at PT. WOM Finance in determining the new Credit Marketing Oficer (CMO) candidate still uses a simple system, namely by conducting interviews directly with CMO candidates. Sometimes a system like this still has many weaknesses including the chosen Credit Marketing Officer that does not meet the required criteria so that the Credit Marketing Officer can not work optimally because in the recruitment process only relies on the interview process and psychological testing. Based on the above problems, PT.WOM Finance requires a system that can help in determining potential employees to become CMOs, namely by building Data Mining applications using the association method. The results of this study are expected to help PT. WOM Finance in determining CMO candidates so that the determination of CMO can be done quickly, precisely and accurately.